The Effect of Entrepreneurship Knowledge on Students' Entrepreneurial Interest at SMK Negeri 1 Makassar - Rosvika Sari; Muhammad Rakib; Agus Syam; M. Ihsan Said Ahmad (Universitas Negeri Makassar, 2023)
The following research aims to ascertain how entrepreneurial knowledge affects the entrepreneurial interest of students of SMK Negeri 1 Makasar. Quantitative research methodology was used in this study and the technique of collecting data used observation, questionnaire, and documentation methods. Students who have learned about entrepreneurship are the target group of the study, and 72 responses are used as the research sample. The method of collecting data using questionnaire data made based on the Liker scale and validated through reliability and validity tests. Analysis was then conducted using simple linear regression. The results showed that entrepreneurial knowledge has a good and clear effect on the desire to do student entrepreneurship at SMKN 1 Makasar. The magnitude of the relationship between entrepreneurial knowledge (X) and entrepreneurial interest (Y) is in the strong group, which is in the interval 0.60-0.799 and the form of a positive correlation where the higher the knowledge of entrepreneurship the higher the desire to do entrepreneurship and vice versa if the lower the knowledge about entrepreneurship, the lower the desire to do entrepreneurship.